2018
DOI: 10.1136/esmoopen-2017-000278
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibition-related colitis: symptoms, endoscopic features, histology and response to management

Abstract: BackgroundImmune checkpoint inhibitors are successfully introduced as anticancer treatment. However, they may induce severe immune-related adverse events (irAEs). One of the most frequent irAEs is diarrhoea. The main objective of this study was to analyse symptoms (ie, grade of diarrhoea), endoscopic and histological features and response to management in immune checkpoint inhibition-related colitis (IRC).Patients and methodsWe retrospectively analysed patients who developed diarrhoea on checkpoint inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
234
3
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(252 citation statements)
references
References 22 publications
11
234
3
4
Order By: Relevance
“…Two studies have reported features of chronic IBD such as mononuclear cell infiltration, granulomas, basal plasmacytosis and crypt abnormalities (atrophy, distortion, branching, budding) in 40% of the patients 24 26. This chronic inflammatory process was found to infiltrate the submucosa in 47% of the patients 24. Another study, however, did not find histological signs of chronic colitis 25.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Two studies have reported features of chronic IBD such as mononuclear cell infiltration, granulomas, basal plasmacytosis and crypt abnormalities (atrophy, distortion, branching, budding) in 40% of the patients 24 26. This chronic inflammatory process was found to infiltrate the submucosa in 47% of the patients 24. Another study, however, did not find histological signs of chronic colitis 25.…”
Section: Resultsmentioning
confidence: 90%
“…Another study, however, did not find histological signs of chronic colitis 25. Apoptotic cells in crypt epithelium have been reported in 42% of patients 24. Microscopic colitis has also been diagnosed in patients treated with anti-CTLA-4 antibodies 25 44 45.…”
Section: Resultsmentioning
confidence: 98%
“…The incidence of GI side effects is reported to be higher and more severe in patients treated with CTLA-4 blocking antibodies as compared with patients receiving PD-1 receptor inhibitors 2 18 19. One of the studies reports that diarrhoea is seen in 35% of patients treated with CTLA-4, 17%–20% in anti-PD-1 and 44% in those treated with combination therapy 13. Another study has shown that treatment-related adverse events of grade 3 or 4 occurred in 16.3% of patients in the nivolumab (anti-PD-1) group, 55% of those in the nivolumab-plus-ipilimumab group (combination therapy) and 27.3% of those in the ipilimumab group (anti-CTLA-4 group), suggesting that the combination therapy increases the risk of irAEs more than either agent used alone 20.…”
Section: Luminal Gi Tract Injury Due To Cpi Therapymentioning
confidence: 99%
“…Common histological findings include an increase in lamina propria cellularity, patchy neutrophilic infiltrate, and in some cases, crypt abscesses. One research group reported an association between endoscopic features and the need for immune suppression beyond high‐dose corticosteroids . These endoscopic findings included the presence of edematous and erythematous mucosa in addition to mucosal ulceration.…”
Section: Immunotherapy‐induced Colitismentioning
confidence: 99%